Association between past exposure to fine particulate matter (PM2.5) and peptic ulcer: A cross-sectional study in eastern China. (February 2021) - Yu, Zhebin; Mao, Xinli; Tang, Mengling; Chen, Yi; Wu, Mengyin; Jin, Mingjuan; Wang, Jianbing; Xu, Lei; Ye, Guoliang; Ding, Jin; Ye, Bin; Chen, Dongya; et al.
Abstract: Ambient fine particulate matter (particle diameter < 2.5 μm, or PM2.5 ) is a major public health concern in China. Exposure to PM2.5 has been associated with a wide range of adverse health outcomes. The current study aimed to estimate the association between exposure to PM2.5 and the risk of peptic ulcer diseases (PUDs). We conducted a hospital-based cross-sectional study of seven major cities in Zhejiang Province, China (combined population > 57 million people), which included a total of 647, 092 subjects who underwent gastroscopy examination (86, 852 subjects were diagnosed with PUDs) recorded in 13 large hospitals from 2014 to 2018. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the relationship between PM2.5 and PUDs, including duodenal ulcers (DUs) and gastric ulcers (GUs). The overall estimated OR (95% CI) associated with every 10-μg/m 3 increase in the 1-month average PM2.5 before the detection of PUDs was 1.050 (95% CI: 1.038, 1.063). The association between PM2.5 concentration and the prevalence of PUDs tended to be attenuated but remained significant when considering different exposure periods (OR = 1.030, 95% CI = 1.018–1.043 for the 3-month moving average; OR = 1.020, 95% CI = 1.005–1.037 for the 6-month moving average). Stronger associations were observed for DUs than GUs. The observed positive association of PM2.5 exposure with PUDs remained significant in the two-pollutant models after adjusting for other air pollutants. Our findings could provide scientific evidence for a more general adverse role of air pollution on PUDs. Highlights: Association of exposure to PM2.5 and peptic ulcer disease was investigated in China. Increased recent exposure to PM2.5 was associated with higher odds for peptic ulcer. The effect of PM2.5 persists when adjusting for other air pollutants. The adverse effect of PM2.5 was stronger on duodenal ulcer than gastric ulcer.